Validating the caregiver self‐efficacy in contribution to self‐care scale Thai version for stroke: A psychometric evaluation - Jom Suwanno; Nuntaporn Klinjun; Kannika Srisomthrong; Matthew Kelly; Marzukee Mayeng; Juk Suwanno (Wiley, 2023)
Abstract Aim To test the validity and reliability of the Caregiver Self‐Efficacy in Contribution to Self‐Care Scale Thai Version (CC‐Self Efficacy Scale (Thai)) for Stroke. Design A cross‐sectional study was undertaken from September to December 2022. Methods Four hundred thirty‐four caregivers of people with stroke were selected from the registry of stroke patients in primary care units or hospitals following inclusion criteria. The research assistants collected information when the caregiver took a patient for a doctor's appointment or visited the patient's and caregiver's home. Results The 434 caregivers had a mean age of 48 years, female 77.67%, 51.97% child or grandchild of patients, and 72.85% living with the patient. Ten items of the CC‐Self Efficacy Scale (Thai) were normally distributed and appropriate for exploratory factor analysis (EFA). EFA suggested three‐factor model. The confirmatory factor analysis (CFA) of the three‐factor model was an unfit model, with the root mean square error of approximation (RMSEA) = 0.09. We regrouped items based on content to create six‐factor model. CFA supported the six‐factor model of CC‐Self Efficacy Scale (Thai) questionnaire with the reliability judged by McDonald's omega being 0.87. The 434 sample size was enough for EFA and CFA. The CC‐Self Efficacy Scale (Thai) with the six‐factor model is appropriate for evaluating the caregiver confidence of people with stroke.